Mitigasi Risiko Pembiayaan Bermasalah Pada Baitul Maal Wat Tamwil Saudara - Alif Muzakki, Muhammad; Purwanto, Purwanto; Fitriyani, Yeny (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Baitul Mal Wat Tamwil (BMT) is a microfinance institution that provides financial services to the community based on Islamic principles. However, a common challenge faced by BMT is problematic financing. This researcher aims to determine the factors that cause financing risk and mitigate the risk of financing problems at BMT Brothers. A descriptive method with a qualitative approach was used because it can provide a comprehensive picture of how financing risk mitigation was carried out with BMT leaders as research respondents in November – December 2023. The research results were obtained by knowing the factors causing financing problems (internal and external), and then conducting a 6C analysis to mitigate financing risks. The research conclusion is that risk mitigation is important in maintaining member trust and reducing the risk of financing problems at your BMT. The limitation of this research is that it does not use quantitative methods and only examines one BMT. It is hoped that the research can provide input for further research to develop the analytical methods used and increase knowledge for further research.